Pastorale berading aan persone geaffekteer deur MIV - Minnie, Francois G. (Koers, 2012)
Pastoral counselling to people affected by HIV.HIV is a pandemic which influences each and everyone in South Africa, the country in the world with the largest number of people living with HIV. The impact of HIV on the social, economical and micro level is tremendous. The effect of HIV on individual households is immediate, and poverty, sickness, stress, death and loneliness contribute to the devastation caused by this phenomenon.The pastoral counsellor should be equipped with the necessary knowledge to guide and support the person affected by HIV. The counselee must be empowered to handle his or her specific crisis significantly. Perspectives based on Scripture suggest how the Christian believer can manage sickness, suffering and death. The Scripture guides the Christian in times of suffering and conflict to persevere in the hope that God will give deliverance. In the article, it will be shown how the pastoral counsellor must, according to Scripture and as a called shepherd, admonish, educate, support and guide the counselee to accept the ministry of reconciliation, given to her or him by God through Christ his Son. The counselee affected by HIV will have to be empowered by the necessary knowledge in order to care for and support the person affected by HIV and be able to digest and cope with his or her own pain and stress. Pastoral counsellors can make use of the proposed counselling model in order to counsel persons affected by HIV.